异构系统开放封装的技术分析与实现框架 - 张晓林; 李广建; 曾蕾; 毛军; 刘炜 (情报理论与实践, 2003)
Open wrapping is a mechanism to wrap up heterogeneous systems into open ones through standard expression,open representation and public registration.This paper analyzes the nature and use of open wrapping,the layers of wrapping required and the techniques used for open wrapping such as metadata crosswalks,metadata wrapping,open search protocols and open interface languages.
Keywords: information technology; system development; metadata/heterogeneous system; open wrapping; search protocol